Contradictions in Care: Ward Nurses' Experiences of Work and Management in the Swedish Public Sector. Issue 2 (3rd April 2022) - Selberg, Rebecca; Sandberg, Magnus; Mulinari, Paula
ABSTRACT: In Sweden, austerity politics and market reforms have resulted in a renegotiation of working conditions negatively impacting female-dominated public sector- and welfare state workers. A growing body of research locates the harshening conditions of nurses in a context of colliding logics between professions and professional authority, the specificities of interpersonal work, and public sector restructuring. Feminist scholars also tend to focus on the special character of care work in explaining nurses' growing discontent under austerity. This article starts out from the position that the characteristics of care work are central in understanding care workers' experiences, but the analysis also shows a more general conflict between labor and capital play out in care work. Based on a qualitative analysis interviews with 50 nurses, the article shows that this contradiction is expressed through conflicts over time, management and resources.